Inclusão escolar: pontos e contrapontos - Salomão, Silvia Cristina; Caiado, Kátia Regina Moreno (Revista de Educação PUC-Campinas, 2007)
MANTOAN, T. E. l.; PRIETO, R. G. In: ARANTES, V. A. (Org.). Inclusão Escolar: pontos e contrapontos. São Paulo: Ed. Summus, 2006. 103p.